2017
DOI: 10.1021/acs.jafc.7b02897
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Catalytic Behavior of DFA I-Forming Inulin Fructotransferase from Streptomyces davawensis with Site-Directed Mutagenesis

Abstract: Previously, a α-d-fructofuranose-β-d-fructofuranose 1,2':2,1'-dianhydride (DFA I)-forming inulin fructotransferase (IFTase), namely, SdIFTase, was identified. The enzyme does not show high performances. In this work, to improve catalytic behavior including activity and thermostability, the enzyme was modified using site-directed mutagenesis on the basis of structure. The mutated residues were divided into three groups. Those in group I are located at central tunnel including G236, A257, G281, T313, and A314S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Figure d represents the space-filling model of M1’s structure, where the locations of these 10 residues are clearly shown on the surface of M1, and thus, they may have a direct relation to the rise in the optimum temperature. Previous studies have shown that the rigidity of surface residues is of great importance in the maintenance of protein thermostability. ,, Therefore, it is a common strategy to modify the surface amino acids for enhanced enzyme thermostability. , In addition, much protein-engineering research has revealed that besides the catalytic triads, the amino acids around the active site are crucial to the enzyme activity. , To achieve a thermostability-improved variant with minimum time and cost, three residues, Gly292, Phe269, and Gly264, were chosen as sites for point mutagenesis because (i) Gly292 possesses the highest b -factor value, indicating its flexibility in the structure, and (ii) Phe269 and Gly264 are close to the active site and located on the extruding loop, which might be of conformational importance for substrate binding (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure d represents the space-filling model of M1’s structure, where the locations of these 10 residues are clearly shown on the surface of M1, and thus, they may have a direct relation to the rise in the optimum temperature. Previous studies have shown that the rigidity of surface residues is of great importance in the maintenance of protein thermostability. ,, Therefore, it is a common strategy to modify the surface amino acids for enhanced enzyme thermostability. , In addition, much protein-engineering research has revealed that besides the catalytic triads, the amino acids around the active site are crucial to the enzyme activity. , To achieve a thermostability-improved variant with minimum time and cost, three residues, Gly292, Phe269, and Gly264, were chosen as sites for point mutagenesis because (i) Gly292 possesses the highest b -factor value, indicating its flexibility in the structure, and (ii) Phe269 and Gly264 are close to the active site and located on the extruding loop, which might be of conformational importance for substrate binding (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that double-site and even triple-site variants exhibit superior properties compared with single-site variants. , Therefore, on the basis of the results of enzyme activity, pH stability, thermostability, and kinetics of the double-site variants (R15K–G292P, R15K–F269Y, and R15K–G264P), a triple-site variant, R15K–F269Y–G292P, of Ef ADI was constructed to achieve an enzyme with improved enzyme activity and thermostability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations